Dietary Intake of Vitamin K Is Inversely Associated with Mortality Risk. Issue 5 (19th March 2014) - Juanola-Falgarona, Martí; Salas-Salvadó, Jordi; Martínez-González, Miguel Ángel; Corella, Dolores; Estruch, Ramón; Ros, Emili; Fitó, Montserrat; Arós, Fernando; Gómez-Gracia, Enrique; Fiol, Miquel; Lapetra, José; Basora, Josep; et al.
Abstract: Vitamin K has been related to cardiovascular disease and cancer risk. However, data on total mortality are scarce. The aim of the present study was to assess the association between the dietary intake of different types of vitamin K and mortality in a Mediterranean population at high cardiovascular disease risk. A prospective cohort analysis was conducted in 7216 participants from the PREDIMED (Prevención con Dieta Mediterránea) study (median follow-up of 4.8 y). Energy and nutrient intakes were evaluated using a validated 137-item food frequency questionnaire. Dietary vitamin K intake was calculated annually using the USDA food composition database and other published sources. Deaths were ascertained by an end-point adjudication committee unaware of the dietary habits of participants after they had reviewed medical records and linked up to the National Death Index. Cox proportional hazard models were fitted to assess the RR of mortality. Energy-adjusted baseline dietary phylloquinone intake was inversely associated with a significantly reduced risk of cancer and all-cause mortality after controlling for potential confounders (HR: 0.54; 95% CI: 0.30, 0.96; and HR: 0.64; 95% CI: 0.45, 0.90, respectively). In longitudinal assessments, individuals who increased their intake of phylloquinone or menaquinone during follow-up had a lower risk of cancer (HR: 0.64; 95% CI: 0.43, 0.95; and HR: 0.41; 95% CI: 0.26, 0.64, respectively) and all-cause mortality (HR: 0.57; 95% CI: 0.44, 0.73; and HR: 0.55; 95% CI: 0.42, 0.73, respectively) than individuals who decreased or did not change their intake. Also, individuals who increased their intake of dietary phylloquinone had a lower risk of cardiovascular mortality risk (HR: 0.52; 95% CI: 0.31, 0.86). However, no association between changes in menaquinone intake and cardiovascular mortality was observed (HR: 0.76; 95% CI: 0.44, 1.29). An increase in dietary intake of vitamin K is associated with a reduced risk of cardiovascular, cancer, or all-cause mortality in a Mediterranean population at high cardiovascular disease risk. This trial was registered at http://www.controlled-trials.com as ISRCTN35739639.